2008
DOI: 10.7863/jum.2008.27.11.1607
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Kidney Insonation With Microbubble Contrast Agents Does Not Cause Renal Tissue Damage in a Porcine Model

Abstract: Objective. Knowledge and quantification of the microcirculation are very important for estimating the status of an organ. Real-time contrast-enhanced sonography assesses microvascular tissue perfusion. This technique has been proposed as innocuous; however, data from experimental animals (rats) have shown renal interstitial microhemorrhage after the procedure. Therefore, we developed a porcine model to explore potential renal damage that in situ exposure might cause. Methods. Kidneys from 8 anesthetized pigs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Subsequent studies have been performed in rat (13,31,41), rabbit (59), dog (63,64,68), swine (24,69), mouse (55,57), and isolated organs (54). Contrast ultrasound imaging of the kidney is not in widespread clinical use, although studies have demonstrated potential utility for evaluation of focal abnormalities (46) and in identifying rejection following renal transplant (14,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have been performed in rat (13,31,41), rabbit (59), dog (63,64,68), swine (24,69), mouse (55,57), and isolated organs (54). Contrast ultrasound imaging of the kidney is not in widespread clinical use, although studies have demonstrated potential utility for evaluation of focal abnormalities (46) and in identifying rejection following renal transplant (14,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Some concerns have been raised about the safety of this procedure. Jiménez and colleagues [28] showed in a porcine model that repeated insonification of the kidney at high MI did not produce any histological change either immediately after the procedure or 4 hours later. There were no signs of inflammatory response and no signs of extravasation of erythrocytes from the capillary system.…”
Section: Contrast-enhanced Ultrasoundmentioning
confidence: 99%
“…The rationale for contact scanning of the kidney was not clear, particularly since the method does not allow clear imaging of the proximal cortex for normal settings of the focal zone depth. No visual or histological evidence of GCH in the proximal cortex or other renal tissue damage was found in this porcine model of CEDUS [7]. These contradictory results for rats and pigs are puzzling and worthy of further investigation.…”
Section: Introductionmentioning
confidence: 90%
“…This present study was undertaken to assess possible renal tissue damage in pigs using methods which replicated, as much as possible, the methods which would be used in humans. In addition, methods similar to those of Jimenez et al [7] were tested in order to understand the origin of the contradictory results.…”
Section: Introductionmentioning
confidence: 99%